Conrad and history - Niland, Richard, 1978- (Oxford English monographs., 2010)
This text analyses the relationship between Conrad's work and three major subjects: the philosophy of history, nationalism (in Europe and Latin America), and Conrad's interest in French Romanticism and Napoleon Bonaparte.